2009
DOI: 10.1287/mnsc.1090.1059
|View full text |Cite
|
Sign up to set email alerts
|

Inference from Streaks in Random Outcomes: Experimental Evidence on Beliefs in Regime Shifting and the Law of Small Numbers

Abstract: Using data generated from laboratory experiments, we test and compare the empirical accuracy of two models that focus on judgment errors associated with processing information from random sequences. We test for regime-shifting beliefs of the type theorized in Barberis, Shleifer, and Vishny (1998) (BSV) and for beliefs in the "law of small numbers" as modeled in Rabin (2002). In our experiments, we show subjects randomly generated sequences of binary outcomes and ask them to provide probability assessments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 19 publications
7
44
0
Order By: Relevance
“…From Figure 2 we see that at Streak jt = 1 there are 2% fewer moves toward numbers than at Streak jt = 0, meaning that there are 2% fewer bets on numbers drawn only in the previous week (and not in consecutive weeks) than on numbers not drawn. Our finding is in the same ballpark as the one found in the lab by Asparouhova et al (2009). They find that, on average, players reduce their probability estimate of continuation by approximately 0.9% for each unit increase in streak length for streaks of length up to three.…”
Section: Aggregate Reaction Of Lotto Players To Recent Drawingssupporting
confidence: 82%
See 1 more Smart Citation
“…From Figure 2 we see that at Streak jt = 1 there are 2% fewer moves toward numbers than at Streak jt = 0, meaning that there are 2% fewer bets on numbers drawn only in the previous week (and not in consecutive weeks) than on numbers not drawn. Our finding is in the same ballpark as the one found in the lab by Asparouhova et al (2009). They find that, on average, players reduce their probability estimate of continuation by approximately 0.9% for each unit increase in streak length for streaks of length up to three.…”
Section: Aggregate Reaction Of Lotto Players To Recent Drawingssupporting
confidence: 82%
“…The authors argue that people who are prone to the gambler's fallacy but are absolutely certain about the true probability underlying random events will continue to act according to the gambler's fallacy even when observing long streaks. 1 Recently, Asparouhova et al (2009) found support for the prediction that the gambler's fallacy turns into the hot hand fallacy for some players in a laboratory experiment where participants are asked to predict the next observation in a random walk process. The authors also show that people are more likely to exhibit the hot hand fallacy as the perception of randomness of the data-generating process decreases.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence comes from laboratory experiments (Haruvy et al, 2007;Asparouhova et al, 2009;Hommes et al, 2008;Beshears et al, 2013;Frydman and Nave, 2016) and survey data (Tortorice, 2012;Greenwood and Shleifer, 2014;Massenot and Pettinicchi, 2017). We suggest that overextrapolation is pervasive as it also applies to expectations formed by firms and about a variable more familiar than, say, inflation or asset prices.…”
Section: Introductionmentioning
confidence: 89%
“…Ayton and Fischer (2004) propose that the hot hand fallacy arises from the experience of positive serial correlations in human action sequences, while the gambler's fallacy arises from the experience of negative recency in sequences of natural events. An experimental study by Asparouhova et al (2009) finds support for the Rabin (2002) model that predicts agents to expect short sequence-ending streaks to reverse (gambler's fallacy) but longer streaks to continue (hot hand fallacy). An increase in perceived randomness increases expectations of reversal to the mean of subjects in this study as well.…”
Section: Introductionmentioning
confidence: 99%